جوگرافیاى مێژوویى ڕۆژهەڵاتى دیجلە لە ئاوێنەى نووسینە شاهانەکانى شەلمانێسەرى سێیەم (٨٥٩-٨٢٤ پ. ز.) دا - أحمد, پ.ى.د.کۆزاد محمد; رجب, هاشم حمە عبدالله; أحمد, پ.ى.د.کۆزاد محمد; رجب, هاشم حمە عبدالله (Sulaimani Journal for Humanities, 2023)
Studying the annals and military campaigns of the Assyrian kings that mention a particular region is essential to understand the history of the region. Careful reading of the royal inscriptions of Shalmaneser III that describe his conquests of certain regions in the east of the Tigris is quite useful in this regard. By analyzing their contents and comparing them with the current geography of the region, in the light of these texts it becomes apparent that the ancient history of Kurdistan must be rewritten. We have tried through this research to analyze the geographical names mentioned in these texts and determine the paths of the campaigns carried out by the Assyrian army in the region.
Keywords: Shalmaneser; Zamua; Namri; Urartu; Media; east of the Tigris; Ancient Kurdistan